Trichilemmal carcinoma, an uncommon tumor: update on its management and prognosis - Pedro Salomão Piccinini; Francisco Carlos Santos Neto; Gibran Busatto Chedid; Jorge Hoyos; Milton Paulo de Oliveira; Carlos Oscar Uebel (Revista Brasileira de Cirurgia Plástica, 2016)
INTRODUCTION: Trichilemmal carcinoma (TC) is a rare neoplasm of skin appendages. It was first described in 1968 as tricoleptocarcinoma, and has an incidence of 0.05% in patients subjected to histopathological examination after excision of cutaneous lesions. TC has an indolent clinical course ; however, reports in the literature put in doubt this indolent behavior. OBJECTIVES: To provide an update on the management and prognosis of TC. METHODS:A search of the PubMed and SciELO databases by using with the MeSH terms "trichilemmal carcinoma", "tricholemmal carcinoma", "adnexal skin tumor", and "carcinoma triquilemal" was performed. RESULTS: Owing to the rarity of TC, most studies were case reports, which essentially corroborate the indolent nature of the disease. Surgical excision is the recommended treatment, and is associated with a low risk of recurrence and low morbidity and mortality. CONCLUSION: The behavior of the lesion and the procedure of treatment of TC are based on isolated cases or in a small series of cases. Because of its low prevalence, a multicenter collaboration of a greater number of cases can help define the best treatment recommendations, pathophysiology, and prognosis. Surgical excision remains the gold standard of treatment, and is associated with a low risk of recurrence.